Discrepancies between parents and teachers of students with autism spectrum disorder (ASD) in executive functioning according to the BRIEF - González Sala, Francisco; Pastor-Cerezuela, Gemma; Sanz-Cervera, Pilar; Tárraga-Mínguez, Raúl (Anales de Psicología / Annals of Psychology, 2023)
One of the critical issues in the assessment of autism spectrum disorder is the behavior exhibited in various developmental contexts, and so assessment by different informants is important in understanding these disorders. The aim of this study was to analyze parent-teacher agreement on executive functioning assessment in a sample of 43 children with autism spectrum disorder with level 2 severity. For this purpose, scores given by parents and teachers on the BRIEF subscales were compared, and the relationship between these scores was analyzed. The results obtained indicated, first, statistically significant differences between parents and teachers on all the scales, with teachers reporting greater executive dysfunction in all cases. Second, there were no statistically significant correlations between the scores given by the two informants on almost all the scales. Overall, these results point to the different perceptions of parents and teachers regarding the executive functions of children with ASD, which may reflect the relevance or role of these functions in the context where they are assessed.